DEVELOPING GLOBAL CITIZENSHIP SKILLS THROUGH EDUCATION GROUNDED IN DEMOCRATIC PRINCIPLES: THEORETICAL AND PRACTICAL PERSPECTIVES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the role of education based on democratic values in shaping global citizenship competencies. It explores the theoretical foundations and historical roots of democratic education, as well as its contemporary practices within education systems. The paper highlights the democratization process of education and its role in developing civic responsibility and critical thinking skills. It emphasizes the importance of democratic education in fostering citizenship competencies and outlines the necessary conditions for the effective implementation of this process.